Solid acid catalyst, its preparation method and application
Patent Information
- Application Number
- CN202611517884.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-29
- Publication Date
- 2026-10-30
AI Technical Summary
中国专利CN106187755A公开了一种以P-Cs-V-Cu-Mo-La-Nd复合氧化物为催化剂合成二异硬脂醇苹果酸酯的方法,但该方法存在以下不足:(1)反应温度高(180-240℃),能耗大且易导致苹果酸热分解;(2)需使用环己烷作为带水剂,增加了溶剂回收成本和工艺复杂性;(3)催化剂组成元素种类多(7种),制备工艺复杂,成本较高
本发明提供的催化剂应用于制备二异硬脂醇苹果酸酯中,反应温度低(100-130℃),可有效抑制苹果酸的热分解和脱水副反应;同时无需添加环己烷等带水剂,简化了工艺流程,降低了生产成本和环境污染;且双酯化选择性高(89-94%),产物收率达到72-78%。
Smart Images

Figure CN122999172A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of catalyst preparation technology, specifically relating to a solid acid catalyst, its preparation method, and its application. Background Technology
[0002] Diisostearyl Malate (CAS No.: 81230-05-9) is an important oily raw material for cosmetics. It has high polarity, excellent pigment dispersibility and skin moisturizing properties, and is widely used in color cosmetics such as lipsticks, lip glosses, and foundations.
[0003] Currently, the industrial production of diisostearyl malate mainly employs liquid strong acids (such as concentrated sulfuric acid and p-toluenesulfonic acid) or titanate catalysts to catalyze the esterification reaction of malic acid with isostearyl alcohol. However, liquid strong acid catalysts suffer from severe equipment corrosion, numerous side reactions, and the generation of large amounts of acidic wastewater during post-treatment; while titanate catalysts, although exhibiting high catalytic activity, are easily decomposed and deactivated upon contact with water, and are difficult to separate and recover from the reaction system.
[0004] Solid acid catalysts have attracted widespread attention in esterification reactions due to their advantages such as ease of separation, reusability, and environmental friendliness. Chinese patent CN106187755A discloses a method for synthesizing diisostearyl malate using P-Cs-V-Cu-Mo-La-Nd composite oxide as a catalyst, but this method has the following shortcomings: (1) high reaction temperature (180-240℃), high energy consumption, and easy thermal decomposition of malic acid; (2) the need to use cyclohexane as a dehydrating agent, which increases the cost of solvent recovery and process complexity; (3) the catalyst has many constituent elements (7 kinds), the preparation process is complicated, and the cost is high. Chinese patent CN109999843A discloses an SO4 2- / ZrO2 type solid superacid catalyst is used for malate esterification. Although the reaction temperature is relatively low (60-100℃), this catalyst is mainly for the esterification of low carbon alcohols such as methanol and ethanol. It has insufficient activity for the esterification of long chain fatty alcohols (such as isostearyl alcohol and C18 branched alcohols). In addition, sulfate ions are easily lost under high temperature hydrothermal conditions, resulting in poor catalyst stability.
[0005] Malic acid molecules contain two carboxyl groups and one hydroxyl group, making them prone to intramolecular dehydration to produce fumaric acid and maleic acid, and intramolecular esterification to produce malic anhydride during esterification. Meanwhile, isostearyl alcohol, being a long-chain branched alcohol, suffers from significant steric hindrance, resulting in a slow esterification rate with malic acid and difficulties in separating the monoesterification and diesterification products. Therefore, developing a solid acid catalyst with high diesterification selectivity suitable for low-temperature esterification of malic acid and isostearyl alcohol is of great significance for reducing production costs and improving product quality. Summary of the Invention
[0006] In view of this, the present invention provides a solid acid catalyst, its preparation method and application. The solid acid catalyst provided by the present invention can efficiently catalyze the esterification reaction of malic acid and isostearyl alcohol at a relatively low temperature, has high diesterization selectivity, and does not require the addition of a dehydrating agent.
[0007] To solve the aforementioned technical problem, the technical solution adopted by the present invention is as follows: A solid acid catalyst, comprising a host and an auxiliary agent; the host is a silicon-aluminum oxide; the auxiliary agent is one or more oxides of molybdenum, tungsten, zirconium, titanium, and cerium; the acid in the catalyst is a Brønsted acid and a Lewis acid, the total acid content of the catalyst is 0.40-0.55 mmol / g, and the molar ratio of Brønsted acid to Lewis acid is 0.7-1.5:1.
[0008] Preferably, the silicon-aluminum molar ratio in the solid acid catalyst is 0.6-3.0; and the content of the auxiliary agent is 5%-20% of the total mass of the catalyst.
[0009] Preferably, the additives are MoO3 and ZrO2, wherein MoO3 accounts for 3%-8% of the total mass of the catalyst and ZrO2 accounts for 2%-6% of the total mass of the catalyst.
[0010] Preferably, the catalyst has a specific surface area of 150-350 m². 2 / g, pore volume 0.3-0.8cm 3 / g, with an average pore size of 5-15nm.
[0011] The present invention also provides a method for preparing the solid acid catalyst according to any one of the above claims, comprising the following steps: 1) Dissolve the silicon source, aluminum source, and auxiliary element salt in deionized water to form a mixed solution; 2) Add the precipitant while stirring, adjust the pH to 8-10, and continue stirring for 4-8 hours to obtain the precipitate; 3) Filter, wash, and dry the precipitate to obtain the dried material; 4) Calcine the dried material to obtain a solid acid catalyst.
[0012] Preferably, the precipitant in step 2) is ammonia, urea or ammonium carbonate.
[0013] Preferably, the drying temperature in step 3) is 100-120℃ and the time is 12-24 hours; the calcination temperature in step 4) is 450-650℃ and the calcination time is 4-8 hours.
[0014] The present invention also provides the application of the solid acid catalyst described in any one of the above-mentioned claims in the preparation of diisostearyl malate.
[0015] Preferably, diisostearyl malate is prepared using the following steps: Malic acid, isostearyl alcohol, and catalyst are mixed and reacted under nitrogen protection. During the reaction, water generated is continuously removed through a water separator to obtain diisostearyl malate.
[0016] Preferably, the molar ratio of malic acid to isostearyl alcohol is 1:2.0-2.5; the amount of catalyst added is 4%-8% of the total mass of malic acid and isostearyl alcohol; the reaction temperature is 100-130℃ and the reaction time is 4-8 hours.
[0017] Compared with the prior art, the beneficial effects of the present invention are as follows: The catalyst provided by this invention is used in the preparation of diisostearyl malate. The reaction temperature is low (100-130℃), which can effectively inhibit the thermal decomposition and dehydration side reaction of malic acid. At the same time, there is no need to add dehydrating agents such as cyclohexane, which simplifies the process and reduces production costs and environmental pollution. Moreover, the diesterization selectivity is high (89-94%), and the product yield reaches 72-78%.
[0018] The catalyst provided by this invention has a simple composition, readily available raw materials, low cost, simple preparation process, and is easy to industrialize. Moreover, the catalyst is easy to separate and can be reused after simple filtration, ethanol washing, and drying. It has stable catalytic activity, is easy to separate and reuse, is environmentally friendly, and the yield decreases by less than 5% after 5 uses. The catalyst has good prospects for industrial application. Attached Figure Description
[0019] Figure 1 The attached diagram shows the N2 adsorption / desorption process of Example 1; Figure 2 The NH3TPD spectrum of Example 1; Figure 3 The image shown is the XRD pattern of Example 1. Detailed Implementation
[0020] The technical solutions in specific embodiments of the present invention will be described in detail and completely below. Obviously, the described embodiments are only some specific implementations of the overall technical solution of the present invention, and not all implementations. Based on the overall concept of the present invention, all other embodiments obtained by those skilled in the art fall within the protection scope of the present invention.
[0021] This invention provides a solid acid catalyst, the catalyst comprising a host and an auxiliary agent; the host is a silicon-aluminum oxide; the auxiliary agent is one or more oxides of molybdenum, tungsten, zirconium, titanium, and cerium; the acid in the catalyst is a Brønsted acid and a Lewis acid, the total acid content of the catalyst is 0.40-0.55 mmol / g, and the molar ratio of Brønsted acid to Lewis acid is 0.7-1.5:1.
[0022] The solid acid catalyst provided by this invention is mainly composed of silicon dioxide and aluminum oxide. The SiO2-Al2O3 composite oxide not only possesses good thermal stability and mechanical strength, but also, in the amorphous SiO2-Al2O3 composite oxide, Al... 3+ With tetracoordination (AlO4) - The form enters the SiO2 network and replaces part of the Si. 4+ Because of Al 3+ With Si 4+ Due to the presence of a charge difference, a bridging Si-OH-Al hydroxyl group, i.e., a Brønsted acid center (B acid center), is formed near each coordinated Al group to maintain the electroneutrality of the framework. Simultaneously, five-coordinated (AlO5) or coordinally unsaturated six-coordinated Al groups... 3+ The coordinating unsaturated centers, namely Lewis acid centers (L-acid centers), are formed by silica and alumina, constituting both Brønsted and Lewis acids. During the malic acid diesterization reaction, the Brønsted acid center is responsible for protonating the malic acid carboxyl group, forming an acyl cation intermediate, while the Lewis acid center is responsible for adsorbing and polarizing the CO bond of isostearyl alcohol, promoting its nucleophilic attack. Excessive Brønsted acid and insufficient Lewis acid result in slow alcohol molecule activation, while excessive Lewis acid induces hydroxyl dehydration and intramolecular esterification. Therefore, this invention controls the molar ratio of Brønsted acid to Lewis acid at 0.7-1.5:1. Maintaining this ratio not only facilitates the gradual activation and esterification of the two carboxyl groups of malic acid but also suppresses the dehydration side reaction of the hydroxyl group.
[0023] However, the SiO2-Al2O3 composite oxide has a low surface acidity and uneven acidity distribution. During calcination, some bridged hydroxyl groups undergo condensation and dehydration, resulting in a significant decrease in total acidity and an imbalanced B / L ratio. If directly used in the esterification reaction of malic acid and isostearyl alcohol, it suffers from insufficient catalytic activity and poor diesterization selectivity. To address this technical problem, this application introduces auxiliary elements (one or more of molybdenum, tungsten, zirconium, titanium, and cerium) onto the SiO2-Al2O3 composite oxide as the main component. These auxiliary elements exist on the support surface in a highly dispersed or amorphous oxide form. Their introduction does not alter the SiO2-Al2O3 framework structure but rather superimposes, modifies, and stabilizes acid centers on the acidic basis of the framework. Synergistically with the auxiliary elements, they achieve a balanced number and moderate strength of the two types of acid centers, balancing reaction rate and diesterization selectivity. The specific functions of each auxiliary element are as follows: (1) MoO3:Mo 6+ It provides L-acid centers of moderate strength, which can polarize the CO bond of isostearyl alcohol and promote nucleophilic attack of sterically hindered long-chain alcohols; at the same time, MoO3 forms Mo-O-Si / Mo-O-Al bonds with hydroxyl groups on the support surface, inhibiting the condensation loss of bridged Si-OH-Al hydroxyl groups during calcination, thus stabilizing the acid centers.
[0024] (2) WO3: W 6+ It provides strong L-acid centers and a certain amount of weak B-acid centers, which can significantly improve the total acid content and low-temperature activity; and the tungsten oxide has good thermal stability and can maintain a highly dispersed state without being easily sintered in the calcination temperature range of 450-650℃.
[0025] (3) ZrO2: The surface has both Zr-OH (B acid) and coordinatively unsaturated Zr. 4+ The amphoteric nature of (L acid) can increase the surface hydroxyl density and repair the partially condensed Si-OH-Al bridged hydroxyl groups during calcination, bringing the B / L molar ratio closer to 1; ZrO2 is particularly beneficial for promoting the second step of esterification from monoester to diester and is a key component for improving diesterification selectivity.
[0026] (4) TiO2: Ti 4+ As an L-acid center, it can enhance the coordination activation of malic acid carbonyl oxygen; at the same time, TiO2 can inhibit the growth of composite oxide grains, refine the pore structure, and improve the accessibility of acid centers.
[0027] (5) CeO2: Ce 4+ / Ce 3+ Redox pairs and surface oxygen vacancies can eliminate trace oxidizing species in the reaction system, inhibit carbon deposition, and improve the thermal and hydrothermal stability of the catalyst, thus extending its service life.
[0028] In this invention, the silicon-to-aluminum molar ratio in the solid acid catalyst is preferably 0.6-3.0, more preferably 0.8-2.0:1; the content of the promoter is preferably 5%-20% of the total mass of the catalyst. According to the above description of the formation of Brønsted acid and Lewis acid, the ratio of SiO2 to Al2O3 (characterized by the Si / Al molar ratio) directly determines the number and relative proportion of these two types of acid centers. When the Al content is too low (Si / Al molar ratio greater than 3.0), the number of bridged Si-OH-Al hydroxyl groups is small and dispersed, the interaction between acid centers is weak, the total acid content of the catalyst drops below 0.35 mmol / g, the malic acid carboxyl protonation rate is insufficient, the esterification reaction rate is slow, and diesterization is difficult to complete. When Al is excessive (Si / Al molar ratio less than 0.5), Al-O-Al bonds aggregate to form an aluminum-rich phase, and the specific surface area and total acid content decrease instead. Simultaneously, the excessively strong Lewis acid centers promote the β-elimination dehydration of malic acid hydroxyl groups, significantly increasing byproducts such as fumaric acid and maleic acid. When the Si / Al molar ratio is controlled within the range of 0.6-3.0, the density of bridged hydroxyl groups is high and their distribution is uniform. With further regulation and stabilization of the acid centers by auxiliary elements, the total acid content of the catalyst can reach 0.40-0.55 mmol / g. Furthermore, as the Si / Al molar ratio increases, the L acid centers (coordinated unsaturated Al) increase. 3+ The rate of decrease in the number of Si / Al sites is faster than that of Brønsted acid centers, resulting in an overall increase in the B / L molar ratio. By matching the Si / Al molar ratio with the types and contents of auxiliary elements, the B / L molar ratio can be stabilized within a suitable range of 0.7-1.5. Adding auxiliary elements inhibits the condensation and dehydration of some bridged hydroxyl groups during calcination, maintaining the total acid content and balancing the B / L ratio.
[0029] In this invention, to further improve the catalytic effect, molybdenum and zirconium are preferably used as auxiliary elements, wherein the content of MoO3 is preferably 3-8 parts and the content of ZrO2 is preferably 2-6 parts. This invention combines MoO3 and ZrO2. MoO3 (Mo being a moderately strong L-acid) mainly contributes L-acid centers to activate long-chain alcohols, while the introduction of ZrO2 increases the surface hydroxyl density, mainly contributing Brønsted acid centers and stabilizing bridging hydroxyl groups. The two work synergistically to achieve a match in terms of acid content, acid strength, and acid type. Combined with a suitable Si / Al ratio framework acid, the total acid content reaches 0.40-0.55 mmol / g, and the B / L molar ratio is 0.7-1.5, simultaneously achieving high conversion rate and high diesterization selectivity at low temperatures.
[0030] In this invention, the specific surface area of the catalyst is preferably 150-350 m². 2 / g, with a preferred pore volume of 0.3-0.8cm³. 3The average pore size is preferably 5-15 nm. In this invention, a suitable pore structure facilitates the diffusion of long-chain isostearyl alcohol molecules within the catalyst channels, reducing side reactions caused by diffusion restriction. Isostearyl alcohol is a C18 branched long-chain alcohol with a molecular dynamic diameter of approximately 0.8-1.2 nm; the extended chain length of diisostearyl malate diester is approximately 2.5 nm. The pore structure affects the reaction rate and diesterization selectivity by influencing the diffusion behavior of reactants and products and the accessibility of acid centers. In this invention, the mesoporous channels with an average pore size of 5-15 nm are significantly larger than the molecular sizes of reactants and products, resulting in low diffusion resistance and high accessibility of acid centers to long-chain molecules within the channels. Simultaneously, water condensed by capillary action within the mesopores can be promptly carried out by nitrogen and continuously removed by a water separator. This, combined with the equilibrium shift mechanism of "excess alcohol + water removal," promotes a positive shift in the esterification equilibrium, achieving high conversion rates without the need for a dehydrating agent. The pore volume is 0.3-0.8 cm³. 3 / g provides storage space for liquid-phase reactants, maintains reactant concentration within the channels, and compensates for the concentration gradient between the bulk phase and the pore phase; specific surface area is 150-350 m². 2 While ensuring the density of acid centers, this invention avoids wasting acid centers due to excessive micropores (where long-chain molecules cannot enter). When the pore size is less than 5 nm, the diffusion of long-chain reactants and products within the pores is restricted, the residence time of reactants is prolonged, monoester intermediates are locally enriched within the pores, and the ortho-carboxyl group of malic acid is prone to intramolecular dehydration to generate fumaric acid and maleic acid, resulting in decreased diesterization selectivity. Furthermore, long-chain products easily clog the pore openings, leading to low acid center utilization and rapid catalyst deactivation. While diffusion is faster when the pore size is greater than 15 nm, the specific surface area decreases sharply, the number of acid centers per unit mass of catalyst decreases, the total acid content is difficult to reach above 0.40 mmol / g, the reaction rate decreases significantly, and the mechanical strength of the catalyst deteriorates. It is understood that the above-mentioned range defined in this invention represents the optimal range, with good catalytic effect and few side reactions.
[0031] The present invention also provides a method for preparing the solid acid catalyst according to any one of the above claims, comprising the following steps: 1) Dissolve the silicon source, aluminum source, and auxiliary element salt in deionized water to form a mixed solution; 2) Add the precipitant while stirring, adjust the pH to 8-10, and continue stirring for 4-8 hours to obtain the precipitate; 3) Filter, wash, and dry the precipitate to obtain the dried material; 4) Calcine the dried material to obtain a solid acid catalyst.
[0032] In this invention, the precipitant in step 2) is preferably ammonia, urea or ammonium carbonate.
[0033] In this invention, the drying temperature in step 3) is preferably 100-120℃, and the drying time is preferably 12-24 hours. In this invention, the calcination temperature in step 4) is preferably 450-650℃, and the calcination time is preferably 4-8 hours. In this invention, by controlling the calcination temperature within this range, the Si / Al ratio, and employing co-precipitation pH and stirring, the pore size of the primary pores is controlled within the mesoporous range. In this invention, the calcined material can be subjected to forming treatment as needed, with forming methods including extrusion, tableting, or spray drying.
[0034] The present invention also provides the application of the solid acid catalyst described in any one of the above-mentioned claims in the preparation of diisostearyl malate.
[0035] In this invention, the diisostearyl malate is preferably prepared using the following steps: Malic acid, isostearyl alcohol, and catalyst are mixed and reacted under nitrogen protection. During the reaction, water generated is continuously removed through a water separator to obtain diisostearyl malate.
[0036] In this invention, the preferred molar ratio of malic acid to isostearyl alcohol is 1:2.0-2.5. In this invention, by controlling the alcohol-acid molar ratio to 2.0-2.5:1, isostearyl alcohol is in excess, and a water separator is used to continuously remove the water generated in the reaction, thus disrupting the esterification reaction equilibrium and improving the conversion rate of malic acid and the selectivity of diesterization.
[0037] In this invention, the amount of catalyst added is preferably 4%-8% of the total mass of malic acid and isostearyl alcohol; the reaction temperature is preferably 100-130℃, more preferably 110-120℃; and the reaction time is preferably 4-8 hours, more preferably 5-6 hours. In this invention, after the reaction is completed, the catalyst is preferably separated by filtration, and unreacted isostearyl alcohol is recovered by vacuum distillation.
[0038] To further illustrate the present invention, the technical solutions provided by the present invention will be described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0039] Example 1 Catalyst preparation: Weigh out 156g of tetraethyl orthosilicate (TEOS, SiO2 content 28.8%), 221g of aluminum nitrate nonahydrate, and ammonium molybdate tetrahydrate ((NH4)6Mo7O 246.7 g of zirconium nitrate pentahydrate (Zr(NO3)4·5H2O) and 12.2 g of zirconium nitrate pentahydrate (Zr(NO3)4·5H2O) were dissolved in 500 mL of deionized water and stirred vigorously at room temperature for 1 hour to form a homogeneous solution. 25 wt% ammonia was added dropwise under continuous stirring to adjust the pH to 9.0, and stirring was continued for 6 hours. The precipitate was vacuum filtered and washed with deionized water until the pH of the filtrate reached 7.0. The filter cake was dried at 110℃ for 18 hours, ground, and then calcined in a muffle furnace at a temperature increased to 550℃ at 2℃ / min for 6 hours. After natural cooling to room temperature, the solid acid catalyst Cat-1 was obtained. Stoichiometrically, the oxide composition of Cat-1 was: SiO2 53.5%, Al2O3 35.8%, MoO3 6.5%, ZrO2 4.2%, with a Si / Al molar ratio of 1.27. No additional binder was added.
[0040] Catalyst characterization: Specific surface area and pore structure were determined using the N2 adsorption-desorption method (see specific spectral data). Figure 1 As shown), the specific surface area of Cat-1 is 280 m². 2 / g, pore volume 0.55 cm³ 3 / g, with an average pore size of 8.5 nm.
[0041] Total acidity was determined using NH3-TPD (specific spectral data are shown below). Figure 2 As shown in the figure, the total acidity of Cat-1 is 0.45 mmol / g.
[0042] X-ray diffraction (XRD) analysis was performed (specific spectra are shown in the image). Figure 3 As shown in the figure, Cat-1 exhibits characteristic diffraction peaks of SiO2-Al2O3 composite oxides at 2θ=22°, 37°, 45°, and 67°, while no obvious diffraction peaks of MoO3 and ZrO2 crystal phases are observed, indicating that the auxiliary elements exist on the support surface in a highly dispersed or amorphous state.
[0043] Synthesis of diisostearyl malate: 13.4 g (0.1 mol) of L-malic acid, 58.6 g (0.22 mol) of isostearyl alcohol, and 3.5 g of catalyst Cat-1 (4.86% of the total mass of acid and alcohol) were added to a 250 mL three-necked flask. A water separator and a reflux condenser were installed, and nitrogen was introduced for protection. The mixture was heated in an oil bath to 115 °C and stirred for 5.5 hours, with water continuously removed through the water separator. After the reaction was complete, the mixture was cooled to 80 °C, and the catalyst was separated by vacuum filtration. The filtrate was distilled under reduced pressure at 150 °C and -0.095 MPa to recover unreacted isostearyl alcohol, yielding a pale yellow oily product, crude diisostearyl malate. The product composition was analyzed by gas chromatography (GC) with n-hexadecane as an internal standard. The product yield was 76.5%, the diesterization selectivity was 92.3%, and the fumaric acid content in the byproducts was <0.5%, and the malate content was <7%.
[0044] Example 2 Catalyst preparation: Weigh out 146g of tetraethyl orthosilicate, 243g of aluminum nitrate nonahydrate, and ammonium metatungstate ((NH4)6H2W). 12 O 40 6.4 g of zirconium nitrate pentahydrate and 12.2 g of zirconium nitrate pentahydrate were dissolved in 500 mL of deionized water and stirred vigorously for 1 hour. The pH was adjusted to 9.5 by adding 25 wt% ammonia solution, and stirring was continued for 5 hours. The solution was filtered, washed until neutral, dried at 105 °C for 20 hours, and calcined at 580 °C for 5 hours to obtain catalyst Cat-2. The calculated oxide composition was: SiO2 49.7%, Al2O3 39.0%, WO3 7.1%, ZrO2 4.1%, with a Si / Al molar ratio of 1.08.
[0045] Catalyst characterization: Specific surface area: 265 m² 2 / g; pore volume: 0.52 cm³ 3 / g; Average pore size: 9.2 nm; Total acidity: 0.48 mmol / g; Brønsted acidity: 0.22 mmol / g; Lewis acidity: 0.26 mmol / g; B / L molar ratio: 0.85.
[0046] Synthesis of diisostearyl malate: 13.4 g (0.1 mol) of L-malic acid, 62.0 g (0.233 mol) of isostearyl alcohol, and 4.0 g of Cat-2 catalyst (5.3% of the total mass of acid and alcohol) were added to a 250 mL three-necked flask. A water separator and a reflux condenser were installed, and nitrogen was introduced for protection. The mixture was heated in an oil bath to 110 °C and stirred for 6.0 hours, with water continuously removed through the water separator. After the reaction was complete, the mixture was cooled to 80 °C, and the catalyst was separated by vacuum filtration. The filtrate was distilled under reduced pressure at 150 °C and -0.095 MPa to recover unreacted isostearyl alcohol, yielding a pale yellow oily product, crude diisostearyl malate. The product composition was analyzed by gas chromatography (GC) with n-hexadecane as an internal standard. The GC results showed a product yield of 74.8%, a diesterization selectivity of 90.8%, fumaric acid content <0.6%, and malic acid monoester content <8%.
[0047] Example 3 Catalyst preparation: Weigh 150g of 30wt% silica sol (equivalent to 45g of SiO2), 221g of aluminum nitrate nonahydrate, 7.4g of ammonium molybdate tetrahydrate, and 5.1g of cerium nitrate hexahydrate (Ce(NO3)3·6H2O), and dissolve them in 500mL of deionized water. Stir vigorously for 1.5 hours. Add 25wt% ammonia water dropwise to adjust the pH to 8.5, and continue stirring for 7 hours. Filter, wash, dry at 120℃ for 15 hours, and calcine at 520℃ for 7 hours to obtain catalyst Cat-3. The calculated oxide composition is: SiO2 54.2%, Al2O3 36.1%, MoO3 7.3%, CeO2 2.4%, with a Si / Al molar ratio of 1.27.
[0048] Catalyst characterization: Specific surface area: 295 m² 2 / g; pore volume: 0.58 cm³ 3 / g; Average pore size: 7.8 nm; Total acidity: 0.50 mmol / g; Brønsted acidity: 0.24 mmol / g; Lewis acidity: 0.26 mmol / g; B / L molar ratio: 0.92.
[0049] Synthesis of diisostearyl malate: 13.4 g (0.1 mol) of L-malic acid, 60.5 g (0.227 mol) of isostearyl alcohol, and 4.5 g of Cat-3 catalyst (6.09% of the total mass of acid and alcohol) were added to a 250 mL three-necked flask. A water separator and reflux condenser were installed, and nitrogen was introduced for protection. The mixture was heated in an oil bath to 118 °C and stirred for 5.0 hours, with water continuously removed through the water separator. After the reaction was complete, the mixture was cooled to 80 °C, and the catalyst was separated by vacuum filtration. The filtrate was distilled under reduced pressure at 150 °C and -0.095 MPa to recover unreacted isostearyl alcohol, yielding a pale yellow oily product, crude diisostearyl malate. The product composition was analyzed by gas chromatography (GC) with n-hexadecane as an internal standard. The GC results showed a product yield of 77.2%, a diesterization selectivity of 93.5%, fumaric acid content <0.4%, and malic acid monoester content <6%.
[0050] Example 4 Catalyst preparation: 139 g of tetraethyl orthosilicate, 38 g of boehmite (AlOOH, equivalent to 38 g of Al2O3), 4.3 g of ammonium molybdate tetrahydrate, 3.7 g of ammonium metatungstate, and 10.5 g of zirconium nitrate pentahydrate were weighed and dissolved in 500 mL of deionized water. The mixture was stirred vigorously for 1 hour. 25 wt% ammonia was added dropwise to adjust the pH to 9.2, and stirring was continued for 6 hours. The mixture was filtered, washed, dried at 110 °C for 18 hours, and calcined at 560 °C for 6 hours to obtain catalyst Cat-4. The calculated oxide composition was: SiO2 45.5%, Al2O3 43.2%, MoO3 4.0%, WO3 4.0%, ZrO2 3.4%, with a Si / Al molar ratio of 0.89.
[0051] Catalyst characterization: Specific surface area: 270 m² 2 / g; pore volume: 0.53 cm³ 3 / g; Average pore size: 8.8 nm; Total acidity: 0.46 mmol / g; Brønsted acidity: 0.21 mmol / g; Lewis acidity: 0.25 mmol / g; B / L molar ratio: 0.84.
[0052] Synthesis of diisostearyl malate: 13.4 g (0.1 mol) of L-malic acid, 59.2 g (0.222 mol) of isostearyl alcohol, and 3.8 g of Cat-4 catalyst (5.23% of the total mass of acid and alcohol) were added to a 250 mL three-necked flask. A water separator and reflux condenser were installed, and nitrogen was introduced for protection. The mixture was heated in an oil bath to 112 °C and stirred for 5.5 hours, with water continuously removed through the water separator. After the reaction was complete, the mixture was cooled to 80 °C, and the catalyst was separated by vacuum filtration. The filtrate was distilled under reduced pressure at 150 °C and -0.095 MPa to recover unreacted isostearyl alcohol, yielding a pale yellow oily product, crude diisostearyl malate. The product composition was analyzed by gas chromatography (GC) with n-hexadecane as an internal standard. The GC results showed a product yield of 75.9%, a diesterization selectivity of 91.7%, fumaric acid content <0.5%, and malic acid monoester content <7%.
[0053] Example 5 Catalyst preparation: 153g of tetraethyl orthosilicate, 228g of aluminum nitrate nonahydrate, 5.5g of ammonium molybdate tetrahydrate, 12.2g of zirconium nitrate pentahydrate, and 8.5g of tetrabutyl titanate (Ti(OC4H9)4) were weighed and dissolved in 500mL of deionized water. The mixture was stirred vigorously for 1.2 hours. 25wt% ammonia was added dropwise to adjust the pH to 9.0, and stirring was continued for 6.5 hours. The mixture was filtered, washed, dried at 115℃ for 16 hours, and calcined at 540℃ for 6.5 hours to obtain catalyst Cat-5. The calculated oxide composition was: SiO2 51.8%, Al2O3 36.4%, MoO3 5.3%, ZrO2 4.1%, TiO2 2.3%, with a Si / Al molar ratio of 1.21.
[0054] Catalyst characterization: Specific surface area: 285 m² 2 / g; pore volume: 0.56 cm³ 3 / g; Average pore size: 8.2 nm; Total acidity: 0.47 mmol / g; Brønsted acidity: 0.21 mmol / g; Lewis acidity: 0.26 mmol / g; B / L molar ratio: 0.81.
[0055] Synthesis of diisostearyl malate: 13.4 g (0.1 mol) of L-malic acid, 61.0 g (0.229 mol) of isostearyl alcohol, and 4.2 g of Cat-5 catalyst (5.65% of the total mass of acid and alcohol) were added to a 250 mL three-necked flask. A water separator and reflux condenser were installed, and nitrogen was introduced for protection. The mixture was heated in an oil bath to 116 °C and stirred for 5.2 hours, with water continuously removed through the water separator. After the reaction was complete, the mixture was cooled to 80 °C, and the catalyst was separated by vacuum filtration. The filtrate was distilled under reduced pressure at 150 °C and -0.095 MPa to recover unreacted isostearyl alcohol, yielding a pale yellow oily product, crude diisostearyl malate. The product composition was analyzed by gas chromatography (GC) with n-hexadecane as an internal standard. The GC results showed a product yield of 76.8%, a diesterization selectivity of 92.5%, fumaric acid content <0.5%, and malic acid monoester content <6%.
[0056] Example 6 Catalyst preparation: Weigh out 42g of silica (precipitated SiO2), 35g of γ-Al2O3 powder, 6.1g of ammonium molybdate tetrahydrate, 3.2g of ammonium metatungstate, and 13.9g of zirconium nitrate pentahydrate. Add 300mL of deionized water and stir vigorously for 2 hours to form a homogeneous slurry. Adjust the pH to 9.0 by adding 25wt% ammonia water dropwise, and continue stirring for 6.5 hours. Filter, wash, dry at 110℃ for 20 hours, and calcine at 600℃ for 5 hours to obtain catalyst Cat-6. The calculated oxide composition is: SiO2 47.2%, Al2O3 39.3%, MoO3 5.6%, WO3 3.4%, ZrO2 4.5%, with a Si / Al molar ratio of 1.02.
[0057] Catalyst characterization: Specific surface area: 250 m² 2 / g; pore volume: 0.48 cm³ 3 / g; Average pore size: 9.5 nm; Total acidity: 0.44 mmol / g; Brønsted acidity: 0.19 mmol / g; Lewis acidity: 0.25 mmol / g; B / L molar ratio: 0.76.
[0058] Synthesis of diisostearyl malate: 13.4 g (0.1 mol) of L-malic acid, 57.5 g (0.216 mol) of isostearyl alcohol, and 3.0 g of Cat-6 catalyst (4.23% of the total mass of acid and alcohol) were added to a 250 mL three-necked flask. A water separator and reflux condenser were installed, and nitrogen was introduced for protection. The mixture was heated to 105 °C in an oil bath and stirred for 6.5 hours. Water generated was continuously removed through the water separator. After the reaction was completed, the mixture was cooled to 80 °C, and the catalyst was separated by vacuum filtration. The filtrate was distilled under reduced pressure at 150 °C and -0.095 MPa to recover unreacted isostearyl alcohol, yielding a pale yellow oily product, crude diisostearyl malate. The product composition was analyzed by gas chromatography (GC) with n-hexadecane as an internal standard. The GC results showed a product yield of 72.3%, a diesterization selectivity of 89.5%, fumaric acid content <0.8%, and malate monoester content <9%.
[0059] Example 7 Catalyst preparation: 156 g of tetraethyl orthosilicate, 221 g of aluminum nitrate nonahydrate, 6.1 g of ammonium molybdate tetrahydrate, 12.2 g of zirconium nitrate pentahydrate, and 3.8 g of cerium nitrate hexahydrate were weighed and dissolved in 500 mL of deionized water. The mixture was stirred vigorously for 1 hour. 25 wt% ammonia was added dropwise to adjust the pH to 8.8, and stirring was continued for 6 hours. The mixture was filtered, washed, dried at 115 °C for 18 hours, and calcined at 550 °C for 6 hours to obtain catalyst Cat-7. The calculated oxide composition was: SiO₂ 52.9%, Al₂O₃ 35.4%, MoO₃ 35.9%, ZrO₂ 4.1%, CeO₂ 1.8%, with a Si / Al molar ratio of 1.27.
[0060] Catalyst characterization: Specific surface area: 275 m² 2 / g; pore volume: 0.54 cm³ 3 / g; Average pore size: 8.6 nm; Total acidity: 0.47 mmol / g; Brønsted acidity: 0.21 mmol / g; Lewis acidity: 0.26 mmol / g; B / L molar ratio: 0.81.
[0061] Synthesis of diisostearyl malate: 13.4 g (0.1 mol) of L-malic acid, 58.0 g (0.218 mol) of isostearyl alcohol, and 3.6 g of Cat-7 catalyst (5.04% of the total mass of acid and alcohol) were added to a 250 mL three-necked flask. A water separator and reflux condenser were installed, and nitrogen gas was introduced for protection. The mixture was heated in an oil bath to 114 °C and stirred for 5.3 hours. Water generated was continuously removed through the water separator. After the reaction was completed, the mixture was cooled to 80 °C, and the catalyst was separated by vacuum filtration. The filtrate was distilled under reduced pressure at 150 °C and -0.095 MPa to recover unreacted isostearyl alcohol, yielding a pale yellow oily product, crude diisostearyl malate. The product composition was analyzed by gas chromatography (GC) with n-hexadecane as an internal standard. The GC results showed a product yield of 75.4%, a diesterization selectivity of 91.2%, fumaric acid content <0.6%, and malate monoester content <7%.
[0062] Example 8 Catalyst preparation: Weigh out 146g of tetraethyl orthosilicate, 250g of aluminum nitrate nonahydrate, 5.5g of ammonium molybdate tetrahydrate, 3.7g of ammonium metatungstate, and 10.5g of zirconium nitrate pentahydrate, dissolve them in 500mL of deionized water, and stir vigorously for 1.3 hours. Adjust the pH to 9.3 by adding 25wt% ammonia solution dropwise, and continue stirring for 5.5 hours. Filter, wash, dry at 108℃ for 22 hours, and calcine at 570℃ for 5.5 hours to obtain catalyst Cat-8. The calculated oxide composition is: SiO2 48.3%, Al2O3 39.1%, MoO3 5.2%, WO3 4.0%, ZrO2 3.5%, with a Si / Al molar ratio of 1.05.
[0063] Catalyst characterization: Specific surface area: 260 m² 2 / g; pore volume: 0.51 cm³ 3 / g; Average pore size: 9.0 nm; Total acidity: 0.45 mmol / g; Brønsted acidity: 0.20 mmol / g; Lewis acidity: 0.25 mmol / g; B / L molar ratio: 0.80.
[0064] Synthesis of diisostearyl malate: 13.4 g (0.1 mol) of L-malic acid, 63.2 g (0.237 mol) of isostearyl alcohol, and 4.3 g of Cat-8 catalyst (5.61% of the total mass of acid and alcohol) were added to a 250 mL three-necked flask. A water separator and reflux condenser were installed, and nitrogen was introduced for protection. The mixture was heated in an oil bath to 117 °C and stirred for 5.8 hours, with water continuously removed through the water separator. After the reaction was complete, the mixture was cooled to 80 °C, and the catalyst was separated by vacuum filtration. The filtrate was distilled under reduced pressure at 150 °C and -0.095 MPa to recover unreacted isostearyl alcohol, yielding a pale yellow oily product, crude diisostearyl malate. The product composition was analyzed by gas chromatography (GC) with n-hexadecane as an internal standard. The GC results showed a product yield of 74.1%, a diesterization selectivity of 90.3%, fumaric acid content <0.6%, and malic acid monoester content <8%.
[0065] Example 9 Catalyst preparation: 204 g of tetraethyl orthosilicate, 169 g of aluminum nitrate nonahydrate, and 62.7 g of zirconium nitrate pentahydrate were weighed and dissolved in 500 mL of deionized water. The mixture was stirred vigorously for 1.3 hours. 2 wt% ammonium carbonate was added dropwise to adjust the pH to 9.3, and stirring was continued for 5.5 hours. The mixture was filtered, washed, dried at 108 °C for 22 hours, and calcined at 500 °C for 6 hours to obtain catalyst Cat-9. The calculated oxide composition was: SiO2 59.0%, Al2O3 23.0%, ZrO2 18.0%, with a Si / Al molar ratio of 2.17.
[0066] Catalyst characterization: 240 m 2 / g; Pore volume: 0.56cm 3 / g; Average pore size: 9.0 nm; Total acidity: 0.47 mmol / g; Brønsted acidity: 0.22 mmol / g; Lewis acidity: 0.25 mmol / g; B / L molar ratio: 0.88.
[0067] Synthesis of diisostearyl malate: 13.4 g (0.1 mol) of L-malic acid, 63.2 g (0.237 mol) of isostearyl alcohol, and 4.4 g of Cat-9 catalyst (5.74% of the total mass of acid and alcohol) were added to a 250 mL three-necked flask. A water separator and a reflux condenser were installed, and nitrogen was introduced for protection. The mixture was heated in an oil bath to 119 °C and stirred for 6 hours, with water continuously removed through the water separator. After the reaction was complete, the mixture was cooled to 80 °C, and the catalyst was separated by vacuum filtration. The filtrate was distilled under reduced pressure at 150 °C and -0.095 MPa to recover unreacted isostearyl alcohol, yielding a pale yellow oily product, crude diisostearyl malate. The product composition was analyzed by gas chromatography (GC) with n-hexadecane as an internal standard. The GC results showed a product yield of 78.8%, a diesterization selectivity of 87.2%, fumaric acid content <0.4%, and malate monoester content <10%.
[0068] Comparative Example 1 Catalyst preparation: 13.4 g (0.1 mol) of L-malic acid, 58.6 g (0.22 mol) of isostearyl alcohol, and 2.0 g (2.8% of the total mass of acid and alcohol) of concentrated sulfuric acid (98%) were added to a 250 mL three-necked flask, denoted as catalyst Cat-C1. A water separator and a reflux condenser were installed, and nitrogen gas was introduced for protection. The reaction was carried out at 140 °C for 6.0 h, and the generated water was continuously removed. After the reaction was completed, the mixture was cooled to room temperature, neutralized to pH 7 with saturated sodium bicarbonate solution, and the aqueous phase was removed by liquid-liquid separation. The organic phase was dried over anhydrous sodium sulfate and then distilled under reduced pressure at 150 °C and -0.095 MPa to obtain the product.
[0069] Catalyst characterization: Synthesis of diisostearyl malate: GC analysis results: product yield was 58.2%, diesterization selectivity was 75.6%, fumaric acid content in byproducts was 3.2%, and malic acid monoester content was 18%.
[0070] The results show that using the traditional liquid acid catalyst concentrated sulfuric acid results in a high reaction temperature, severe side reactions, and significantly lower product yield and selectivity compared to the solid acid catalyst of this invention. Furthermore, the post-treatment is complex and generates saline wastewater.
[0071] Comparative Example 2 Catalyst preparation: 167 g of tetraethyl orthosilicate and 331 g of aluminum nitrate nonahydrate were weighed and dissolved in 500 mL of deionized water. The mixture was stirred vigorously for 1 hour. 25 wt% ammonia was added dropwise to adjust the pH to 9.0, and stirring was continued for 6 hours. The mixture was filtered, washed, dried at 110 °C for 18 hours, and calcined at 550 °C for 6 hours to obtain a catalyst, Cat-C2, free of auxiliary elements. The calculated oxide composition was: SiO2 51.7%, Al2O3 48.3%, with a Si / Al molar ratio of 0.91.
[0072] Catalyst characterization: Specific surface area: 220 m² 2 / g; pore volume: 0.42 cm³ 3 / g; Average pore size: 10.5 nm; Total acidity: 0.32 mmol / g; Brønsted acidity: 0.12 mmol / g; Lewis acidity: 0.20 mmol / g; B / L molar ratio: 0.60.
[0073] Synthesis of diisostearyl malate: 13.4 g (0.1 mol) of L-malic acid, 58.6 g (0.22 mol) of isostearyl alcohol, and 3.5 g of Cat-C2 catalyst (4.86% of the total mass of acid and alcohol) were added to a 250 mL three-necked flask. A water separator and a reflux condenser were installed, and nitrogen was introduced for protection. The mixture was heated in an oil bath to 115 °C and stirred for 5.5 hours, with water continuously removed through the water separator. After the reaction was complete, the mixture was cooled to 80 °C, and the catalyst was separated by vacuum filtration. The filtrate was distilled under reduced pressure at 150 °C and -0.095 MPa to recover unreacted isostearyl alcohol, yielding a pale yellow oily product, crude diisostearyl malate. The product composition was analyzed by gas chromatography (GC) with n-hexadecane as an internal standard. The GC results showed a product yield of 63.7%, a diesterization selectivity of 82.4%, a fumaric acid content of 1.5%, and a malic acid monoester content of 14%.
[0074] The results show that although the Si / Al molar ratio of Cat-C1 (0.91) is within the suitable range defined by this invention, due to the absence of auxiliary elements, some bridged Si-OH-Al hydroxyl groups are lost during calcination, resulting in a total acid content of only 0.32 mmol / g and an imbalanced B / L ratio (0.60). The catalytic activity and diesterization selectivity are significantly lower than those of the composite solid acid catalyst of this invention, demonstrating that auxiliary elements are crucial for constructing and stabilizing acid centers and improving catalyst performance.
[0075] Comparative Example 3 Catalyst preparation: 87g of tetraethyl orthosilicate and 442g of aluminum nitrate nonahydrate were weighed and dissolved in 800mL of deionized water, and stirred vigorously for 1 hour. 25wt% ammonia was added dropwise to adjust the pH to 9.0, and stirring continued for 6 hours. The mixture was filtered, washed, dried at 110℃ for 18 hours, and calcined at 550℃ for 6 hours to obtain the catalyst Cat-C3 with an excessively low Si / Al molar ratio. The calculated oxide composition was approximately 29% SiO2 and 71% Al2O3, with a Si / Al molar ratio of 0.35.
[0076] Catalyst characterization: Specific surface area: 180 m² 2 / g; pore volume: 0.35 cm³ 3 / g; Average pore size: 12.0 nm; Total acidity: 0.38 mmol / g; Brønsted acidity: 0.13 mmol / g; Lewis acidity: 0.25 mmol / g; B / L molar ratio: 0.52.
[0077] Synthesis of diisostearyl malate: 13.4 g (0.1 mol) of L-malic acid, 58.6 g (0.22 mol) of isostearyl alcohol, and 3.5 g of Cat-C3 catalyst (4.86% of the total mass of acid and alcohol) were added to a 250 mL three-necked flask. A water separator and reflux condenser were installed, and nitrogen was introduced for protection. The mixture was heated in an oil bath to 115 °C and stirred for 5.5 hours, with water continuously removed through the water separator. After the reaction was complete, the mixture was cooled to 80 °C, and the catalyst was separated by vacuum filtration. The filtrate was distilled under reduced pressure at 150 °C and -0.095 MPa to recover unreacted isostearyl alcohol, yielding a pale yellow oily product, crude diisostearyl malate. The product composition was analyzed by gas chromatography (GC) with n-hexadecane as an internal standard. The GC results showed a product yield of 64.5%, a diesterization selectivity of 78.2%, a fumaric acid content of 3.5%, and a malate monoester content of 16%.
[0078] The results showed that when the Si / Al molar ratio was too low (0.35), Al-O-Al aggregation led to a decrease in specific surface area and total acidity. Furthermore, the excessively strong Lewis acid centers promoted the β-elimination dehydration of malic acid hydroxyl groups, resulting in a significant increase in byproducts such as fumaric acid and a significant decrease in diesterization selectivity.
[0079] Comparative Example 4 Catalyst preparation: 191.0 g of tetraethyl orthosilicate, 275.9 g of aluminum nitrate nonahydrate, and 4.8 g of ammonium metavanadate (NH4VO3) were weighed and dissolved in 500 mL of deionized water. The mixture was stirred vigorously for 1 hour. 25 wt% ammonia was added dropwise to adjust the pH to 9.0, and stirring was continued for 6 hours. The mixture was filtered, washed until neutral, dried at 110 °C for 18 hours, and calcined at 550 °C for 6 hours to obtain the vanadium-based catalyst Cat-C4. The calculated oxide composition was: SiO2 55.0%, Al2O3 37.5%, V2O 57.5%, with a Si / Al molar ratio of 1.24.
[0080] Catalyst characterization: Specific surface area: 180 m² 2 / g; pore volume: 0.35 cm³ 3 / g; Average pore size: 12.0 nm; Total acidity: 0.38 mmol / g; Brønsted acidity: 0.13 mmol / g; Lewis acidity: 0.25 mmol / g; B / L molar ratio: 0.52.
[0081] Synthesis of diisostearyl malate: 13.4 g (0.1 mol) of L-malic acid, 58.6 g (0.22 mol) of isostearyl alcohol, and 3.5 g of Cat-C4 catalyst (4.86% of the total mass of acid and alcohol) were added to a 250 mL three-necked flask. A water separator and reflux condenser were installed, and nitrogen gas was introduced for protection. The mixture was heated in an oil bath to 115 °C and stirred for 5.5 hours, with water continuously removed through the water separator. After the reaction was complete, the mixture was cooled to 80 °C, and the catalyst was separated by vacuum filtration. The filtrate was distilled under reduced pressure at 150 °C and -0.095 MPa to recover unreacted isostearyl alcohol, yielding a pale yellow oily product. The product composition was analyzed by gas chromatography (GC), with n-hexadecane as an internal standard.
[0082] GC analysis results: product yield was 66.8%, diesterization selectivity was 80.5%, fumaric acid content was 2.8%, and malic acid monoester content was approximately 14%.
[0083] It can be seen that although V₂O₅ can increase the acid content, its excessively high acid strength, imbalanced acid type, and poor stability exacerbate side reactions. This indicates that not all metal oxides are beneficial for improving catalytic performance. The five elements Mo, W, Zr, Ti, and Ce specified in this invention can all provide acid centers of moderate strength and adjustable B / L type, which cannot be replaced by other elements (such as V).
[0084] Catalyst stability test Taking catalysts Cat-1, Cat-2, and Cat-3 from Example 1 as examples, their reusability was tested. After each reaction, the catalyst was separated by vacuum filtration, washed three times with anhydrous ethanol, dried at 110°C for 2 hours, and then directly used in the next reaction. The reaction conditions were the same as in each example. Specific test results are shown in Table 1.
[0085] Table 1
[0086] Table 1 shows that the solid acid catalyst of the present invention has good reusability. After five uses, the yield decreased by 3.0 percentage points and the selectivity decreased by 2.5 percentage points, but it still remained at a high level. The decrease in catalyst activity may be attributed to a small amount of carbon deposition and a slight loss of surface acidic centers. After regeneration treatment in an air atmosphere at 550°C, the catalytic activity can be restored to more than 98% of the initial level.
[0087] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A solid acid catalyst, characterized in that, The catalyst comprises a substrate and an auxiliary agent; the substrate is a silicon-aluminum oxide; the auxiliary agent is one or more oxides of molybdenum, tungsten, zirconium, titanium and cerium; the acid in the catalyst is Brønsted acid and Lewis acid, the total acid content of the catalyst is 0.40-0.55 mmol / g, and the molar ratio of Brønsted acid to Lewis acid is 0.7-1.5:
1.
2. The solid acid catalyst according to claim 1, characterized in that, The silicon-aluminum molar ratio in the solid acid catalyst is 0.6-3.0; the content of the auxiliary agent is 5%-20% of the total mass of the catalyst.
3. The solid acid catalyst according to claim 2, characterized in that, The additives are MoO3 and ZrO2, wherein MoO3 accounts for 3%-8% of the total mass of the catalyst and ZrO2 accounts for 2%-6% of the total mass of the catalyst.
4. The solid acid catalyst according to claim 1, characterized in that, The catalyst has a specific surface area of 150-350 m². 2 / g, pore volume 0.3-0.8cm 3 / g, with an average pore size of 5-15nm.
5. The method for preparing the solid acid catalyst according to any one of claims 1-4, characterized in that, Includes the following steps: 1) Dissolve the silicon source, aluminum source, and auxiliary element salt in deionized water to form a mixed solution; 2) Add the precipitant while stirring, adjust the pH to 8-10, and continue stirring for 4-8 hours to obtain the precipitate; 3) Filter, wash, and dry the precipitate to obtain the dried material; 4) Calcine the dried material to obtain a solid acid catalyst.
6. The method according to claim 5, characterized in that, The precipitant mentioned in step 2) is ammonia, urea, or ammonium carbonate.
7. The method according to claim 5, characterized in that, In step 3), the drying temperature is 100-120℃ and the time is 12-24 hours; in step 4), the calcination temperature is 450-650℃ and the calcination time is 4-8 hours.
8. The use of the solid acid catalyst according to any one of claims 1-4 in the preparation of diisostearyl malate.
9. The application according to claim 8, characterized in that, Diisostearyl malate was prepared using the following steps: Malic acid, isostearyl alcohol, and catalyst are mixed and reacted under nitrogen protection. During the reaction, water generated is continuously removed through a water separator to obtain diisostearyl malate.
10. The application according to claim 9, characterized in that, The molar ratio of malic acid to isostearyl alcohol is 1:2.0-2.5; the amount of catalyst added is 4%-8% of the total mass of malic acid and isostearyl alcohol; the reaction temperature is 100-130℃ and the reaction time is 4-8 hours.
Citation Information
Patent Citations
Method for synthesizing diisostearyl malate
CN106187755A
Solid superacid catalyst formalic acid esterification
CN109999843A
